Mental health policy making in South Korea: structural and cultural influences - Shin, Chang-Sik (2004)
This study focuses on the way in which rapid structural changes (such as economic development, urbanisation and other demographic factors, and the economic crisis of 1997) have raised issues that are seen to require a social policy response in the mental health care arena under Confucian governance in South Korea. These structural changes happened over a couple of hundred years in Western Europe but have taken place over only the past 40 years in Korea. The main thrust of the study is on the extent to which the decisions about policy responses to perceived social problems, especially the increasing number of people with mental health problems, are structurally driven or the extent to which they are informed and shaped by Korean politics and culture.